Special Education in the United States of America and the Potential for Benefit in the Kingdom of Saudi Arabia - Alqahtani, Nada Nasser (Journal of Curriculum and Teaching Methodology, 2024)
This study aims to compare the special education systems between the United States and Saudi Arabia, focusing on identifying potential benefits for developing special education in Saudi Arabia. The study adopts a comparative analytical approach to analyze educational policies, curricula, admission systems, early intervention, transitional education, teacher preparation, and assessment methods. The results indicate that the United States provides an inclusive system where all special needs students are accepted into public schools, with advanced individualized teaching methodologies. In contrast, Saudi Arabia relies on a separate education system for special needs students, although there is increasing attention to inclusive education. The study recommends developing early intervention programs in Saudi Arabia to include children from birth and involving universities and the labor market in preparing transitional education plans. Additionally, it suggests improving the training of general education teachers to qualify them to work with special needs students. The study also proposes the application of multiple assessment methodologies to meet the different needs of students. The findings emphasize the importance of adopting inclusive teaching methods and adapting the national curricula to meet the needs of students with special needs.
Keywords: special education; inclusive education; early intervention; transitional education; educational system comparison